2011
DOI: 10.4049/jimmunol.1002514
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation by Zoledronic Acid in Human Myeloma: An Advantageous Cross-Talk between Vγ9Vδ2 T Cells, αβ CD8+ T Cells, Regulatory T Cells, and Dendritic Cells

Abstract: Vγ9Vδ2 T cells play a major role as effector cells of innate immune responses against microbes, stressed cells, and tumor cells. They constitute <5% of PBLs but can be expanded by zoledronic acid (ZA)-treated monocytes or dendritic cells (DC). Much less is known about their ability to act as cellular adjuvants bridging innate and adaptive immunity, especially in patients with cancer. We have addressed this issue in multiple myeloma (MM), a prototypic disease with several immune dysfunctions that also af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 47 publications
(90 reference statements)
6
91
0
Order By: Relevance
“…68 Extracellular concentrations of IPP were found to be 1000 times higher than the intracellular levels. 69 The importance of IPP was confirmed by the abrogation of the proliferative effect by adding simvastatin or mevastatin to the pretreatment of DCs. 44,68,69 Statins, a common group of cholesterol-lowering drugs, have an inhibiting effect on the mevalonate pathway by blocking the rate-limiting enzyme in the cholesterol synthesis, the HMG-CoA reductase.…”
Section: Mechanisms Behind Dc-mediated Gd T Cell Activationmentioning
confidence: 88%
“…68 Extracellular concentrations of IPP were found to be 1000 times higher than the intracellular levels. 69 The importance of IPP was confirmed by the abrogation of the proliferative effect by adding simvastatin or mevastatin to the pretreatment of DCs. 44,68,69 Statins, a common group of cholesterol-lowering drugs, have an inhibiting effect on the mevalonate pathway by blocking the rate-limiting enzyme in the cholesterol synthesis, the HMG-CoA reductase.…”
Section: Mechanisms Behind Dc-mediated Gd T Cell Activationmentioning
confidence: 88%
“…However, given the functional plasticity of Vc9/Vd2 T cells [49], it remains to be investigated whether under certain conditions they may also instruct DCs to polarize naive CD4 + T cells toward other phenotypes (Th2, Th17, Th22, Treg). Futhermore, little is known about the potential of cd T cell-matured DCs to induce CD8 + T cell responses [50]. While it has been shown that induction of cytotoxic T cells requires TLR stimulation of DCs [51], it will be interesting to test whether Vc9/Vd2 T cell mediated maturation can overcome this necessity, and whether CD8 + T cell phenotypes can be similarly regulated as their CD4 + T cell counterparts [52].…”
mentioning
confidence: 99%
“…A number of immunomodulatory effects of N-BPs have been described (3,(11)(12)(13)(14)(15). The ability of N-BPs to stimulate gd T cells was discovered more incidentally when patients with bone disease had increased frequencies of gd T cells after their first pamidronate administration (9).…”
mentioning
confidence: 99%